Factors influencing outcomes of severely injured children in a South African context - Koekemoer, Heinrich Pieter (My University, 2017)
INTRODUCTION Paediatric trauma is a significant health burden and a leading cause of death among children in South Africa and globally. OBJECTIVE To determine the factors influencing the outcomes of severely injured children in a South African context. METHODS A retrospective study on factors influencing mortality in a paediatric cohort (≤ 14 years) admitted to the intensive care units of two hospitals in Gauteng, South Africa, from 1 January 2006 to 31 December 2013 after suffering major trauma (ISS>10). RESULTS The total cohort (n=166) consisted of public (n=125) and private (n=41) cohorts with actual death 15.7% (n=26) of the total cohort. There was a significant difference in probability of survival in survivors (92%) versus deaths (82%) (p=0.004). Factors that influenced the risk of mortality included time spent in the paediatric ICU [odds ratio of 0.706 (95% CI, 0.544- 0.915)] and whether a patient received public or private care [odds ratio of 5.43 (95% CI, 1.178-25.012)]. Both the Injury Severity Score (p=0.004) and Revised Trauma Score (p=0.034) systems played a significant role in the ability to predict mortality. CONCLUSION The outcome of severe paediatric trauma is influenced by multiple factors. The strongest predictors of mortality according to this study are time spent in PICU and the private health sector; numerous limitations of this study require replication with much larger data sets using paediatric specific trauma outcome scores.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Medicine in the branch of Paediatrics Johannesburg 2017.
Keywords: Pediatrics; Advanced Trauma Life Support Care (Severely Injured); Child Mortality